Intravascular Ultrasound-guided Versus Angiography-guided Percutaneous Coronary Intervention: Evidence from Observational Studies and Randomized Controlled Trials - Xiao-Fei Gao; Xiang-Quan Kong; Guang-Feng Zuo; Zhi-Mei Wang; Zhen Ge; Jun-Jie Zhang (US Cardiology Review)
Coronary angiography has been considered the gold standard for the diagnosis of coronary artery disease and guidance of percutaneous coronary intervention (PCI). However, 2D-projection angiography cannot completely reflect the 3D coronary lumen. Intravascular ultrasound (IVUS) can overcome a number of limitations of coronary angiography by providing more information about the dimensions of the vessel lumen, plaque characteristics, stent deployment, and the mechanisms of device failure. Growing data from observational studies and randomized controlled trials have confirmed the clinical benefit of IVUS guidance during PCI. This article summarizes the evidence regarding IVUS guidance to highlight its advantages and to support the use of IVUS during PCI.